Casas, património, civilização. Nomos versus physis no Pensamento Grego - Maria do Céu Fialho (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2019)
This study about two concepts wants to recuperate, under a literary and philosophic perspective, the famous antithesis originated in Classical Athens, and transfered through the occidental cultures along the centuries. Therefore, retaking the arguments of past discussions, nómos versus phýsis are considered in their process of transmission and reception.